IMPLEMENTASI INDONESIA PAKISTAN PREFERENTIAL TRADE AGREEMENT (IP-PTA) OLEH INDONESIA - Yuszuraini "; Irwan Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study analyzes how the implementation of the Indonesia Pakistan Preferential Trade Agreement (IP-PTA) by Indonesia in 2013-2018. IP-PTA is a trade agreement between Indonesia and Pakistan covering certain products and for a limited time. This trade agreement was signed by the two countries in 2012 and began to be implemented in 2013. Currently, Indonesia has established many PTA with other countries. Therefore, this study aims to see how the implementation of the trade agreement.            This study uses qualitative research methods with primary data obtained through interviews as well as secondary data derived from various existing reading sources such as books, journals, newspapers, and others. This study uses the Perspective of Liberalism, Level of Nation-State Analysis, and International Cooperation Theory.             The results of this study show that Indonesia implements IP-PTA in several ways namely, ratifying the IP-PTA through Presidential Regulation No. 98/2012, facilitate and reduce trade barriers by giving preferential tariffs to the products listed in the agreed agreements, as well as reviewing the Pakistan joint agreement to see how the development of the IP-PTA in each country. The review was carried out three times before two countries agreed to continue the plan to expand trade cooperation.Keywords: Preferential Trade Agreement, Implementation.